1982
DOI: 10.1126/science.217.4560.647
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Synthetic Allatotoxins: Suicide Substrates for Juvenile Hormone Biosynthesis

Abstract: Cytotoxic agents with antijuvenile hormone activity in insects have been discovered. Their mechanism of action may involve an oxidative bioactivation into a reactive quinone methide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…It has been postulated that the precocenes undergo an oxidative activation forming highly reactive epoxides [17l capable of destructive alkylation of the allatal tissues. Similarly, we have suggested that the IPP could, through a similar oxidative activation, form either reactive epoxides or quinone methides capable of an identical cytotoxic action [20]. The allatal atrophy following the destruction of the parenchymal cells by allatotoxins and its subsequent invasion by connective tissue has been well established [6,7,11,27,28].…”
Section: Discussionmentioning
confidence: 96%
“…It has been postulated that the precocenes undergo an oxidative activation forming highly reactive epoxides [17l capable of destructive alkylation of the allatal tissues. Similarly, we have suggested that the IPP could, through a similar oxidative activation, form either reactive epoxides or quinone methides capable of an identical cytotoxic action [20]. The allatal atrophy following the destruction of the parenchymal cells by allatotoxins and its subsequent invasion by connective tissue has been well established [6,7,11,27,28].…”
Section: Discussionmentioning
confidence: 96%
“…Precocene II metabolized by monooxygenase enzymes to a highly labile epoxide may then alkylate cell macromolecules (Aizawa et al, 1985;Bowers et al, 1982). Precocene II present in H. zea larvae for days may be subject to metabolism by mixed-function oxidases in tissues other than the midgut.…”
Section: Discussionmentioning
confidence: 99%
“…Oncopeltus fasciatus responded to the open-chain analogues (29 b) and (29 c) but not to (29 a), whereas L. migratoria was unaffected by these compounds. Bowers et al (1982) suggested that analogue (29 c) may be oxidatively converted into the corresponding o-quinone methide, which may react directly with cellular nucleophiles rather than through the mechanistically more likely formation of precocene analogue (28 c). This mechanism is illustrated in figure 4 for the related compound (29 b).…”
Section: Insect Growth Regulatorsmentioning
confidence: 98%